Biogeography of Abyssocythere and Dutoitella (Ostracoda), with descriptions of three new species - Brandão, Simone N.; Stuhlmann, Annalena; Vital, Helenice; Brandt, Angelika (Zootaxa, 2016)
Ostracods have an extensive fossil record and are widely applied in palaeoenvironmental reconstructions. Here, we investigate the biogeography of two common and widespread genera, Abyssocythere and Dutoitella. Both appeared in the Cretaceous and are widely distributed in modern deep seas, but all species are restricted in distribution. The earliest record of Dutoitella is from shallow water, while the earliest Abyssocythere is from the deep sea. The Southern Ocean/Southern Atlantic seem to have been the area where both genera originated, and from which they eventually colonised other oceans. Dutoitella diversified into at least eleven species during Campanian-Eocene times, and by the end of the Eocene, the genus had spread to the Indian Ocean. This pattern continued after the establishment of the psychrosphere into the Neogene, with the development of numerous Miocene species. Abyssocythere, with 15 species, while also diversifying in the late Cretaceous South Atlantic, appears to have developed fewer species than Dutoitella. Finally, we describe three new species from the Southern Ocean (Abyssocythere bensoni sp. nov., Dutoitella karanovicae sp. nov. and Dutoitella richarddinglei sp. nov.), re-illustrate the types of Abyssocythere squalidentata (Brady, 1880) and Dutoitella suhmi (Brady, 1880), and study the soft parts of the genus Dutoitella, which were previously undocumented.